2014
DOI: 10.32607/20758251-2014-6-2-95-105
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a pIX-modified Adenovirus Vector Able to Effectively Bind to Nanoantibodies for Targeting

Abstract: Current targeting strategies for genetic vectors imply the creation of a specific vector for every targeted receptor, which is time-consuming and expensive. Therefore, the development of a universal vector system whose surface can specifically bind molecules to provide efficient targeting is of particular interest. In this study, we propose a new approach in creating targeted vectors based on the genome of human adenovirus serotype 5 carrying the modified gene of the capsid protein pIX (Ad5-EGFP-pIX-ER): recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…They include increasing the hydrodynamic radius of a protein by attaching highly flexible and hydrophilic molecules such as polyethylene glycol (PEG) and carbohydrates or by genetic fusion with polypeptide chains mimicking the biochemical properties of PEG, fusion of V H H to the Fc region of IgG, fusion or non-covalent binding to albumin ( 104 ) ( Figure 2D ). Nanobodies can also be used as modules to engineer larger molecules with several valencies and/or specificities, such as multivalent ( 105 108 ), bispecific ( 105 , 109 ), and other ( 110 , 111 ) constructs that may acquire considerably higher specificity, binding efficiency and biological activity ( 106 , 107 , 111 ). Nanobodies were also considered as possible ligands to design new highly specific immunosorbents ( 112 114 ).…”
Section: Evaluation Of the Suitability Of Allergen-specific Nanobodiementioning
confidence: 99%
“…They include increasing the hydrodynamic radius of a protein by attaching highly flexible and hydrophilic molecules such as polyethylene glycol (PEG) and carbohydrates or by genetic fusion with polypeptide chains mimicking the biochemical properties of PEG, fusion of V H H to the Fc region of IgG, fusion or non-covalent binding to albumin ( 104 ) ( Figure 2D ). Nanobodies can also be used as modules to engineer larger molecules with several valencies and/or specificities, such as multivalent ( 105 108 ), bispecific ( 105 , 109 ), and other ( 110 , 111 ) constructs that may acquire considerably higher specificity, binding efficiency and biological activity ( 106 , 107 , 111 ). Nanobodies were also considered as possible ligands to design new highly specific immunosorbents ( 112 114 ).…”
Section: Evaluation Of the Suitability Of Allergen-specific Nanobodiementioning
confidence: 99%
“…However, expressing these retargeting molecules separately and then assembling them with virus particles into a functional complex before delivery has not been easy either. Synthetic leucine-zipper-based dimers [146,147] and bispecific T-cell engagers (BiTEs) are examples of retargeting molecules that may need extensive maturation. Several studies have tried to use them to increase tumor specificity, however the overall outcomes have not been significant [147][148][149][150][151][152][153][154][155].…”
Section: Soluble Receptors Conjugated To Ligandsmentioning
confidence: 99%
“…Antibody-antibody-based bridging molecules Anti-AdV protein conjugated to VEGFR, TIE-2, integrins, EPCAM, EGFR, HER2, Endoglin, HMWMAA [127][128][129][130][131][132] Antibody-ligand-based bridging molecules anti-AdV protein conjugated to Folate, TNFa, IGF1, EGF [133,134] Peptide-antibody-based bridging molecules p75 neurotropin receptor on hepatic stellate cells [135] Soluble receptors conjugated to ligands (sCAR, FX) EGF, anti-Cd40 ScFv, ApoE ligand, anti-ErbB2, anti-CEA, Polysialyc-acid (PSA), CXCL12 [136][137][138][139][140][141][142][143][144][145] BiTE, Leucine-zipper-based linkers CD44v6, anti-B-cell maturation antigen, FR-α, EGFR, EpCAM, carcinoembryonic antigen, CD40 [147][148][149][150][151][152][153][154] b. Selective Expression of Effectors (Inhibitors/Enhancers) in Specific Cells.…”
Section: Retargeting Of Adv By Affinity Modifiersmentioning
confidence: 99%
“…We hypothesized that a tumor-targeted Ad vector can be achieved via highly specific association with secreted bioactive TRAIL proteins by employing synthetic leucine zipper-like dimerization domains (zippers) that have been optimized for structural compatibility between the Ad capsid and TRAIL. The feasibility and effectiveness of such strategy has been confirmed by M. N. Garas' study recently [26]. In this report, based on a 24-base-pair deletion mutant E1A oncolytic Ad (Δ24E1A) [27–29], we outlined the biochemical analysis, functional validation and anti-tumor activity of a novel TRAIL-modified Ad vector and demonstrated that this engineered Ad virion with TRAIL on the surface could target cancer tissues administered by IV injection in vivo .…”
Section: Introductionmentioning
confidence: 75%